Respuesta :
The recursive formula of the explicit formula [tex]A_n = 3 + 2n[/tex] is [tex]A_n = A_{n-1} + 2[/tex]
The explicit formula is given as:
[tex]A_n = 3 + 2n[/tex]
When n = 1, we have:
[tex]A_1 = 3 + 2(1)[/tex]
[tex]A_1 = 5[/tex]
When n = 2, we have:
[tex]A_2 = 3 + 2(2)[/tex]
[tex]A_2 = 7[/tex]
When n = 3, we have:
[tex]A_3 = 3 + 2(3)[/tex]
[tex]A_3 = 9[/tex]
So, we have:
[tex]A_1 = 5[/tex]
[tex]A_2 = 7[/tex]
[tex]A_3 = 9[/tex]
Rewrite the functions as follows:
[tex]A_1 = 5[/tex]
[tex]A_2 = 5 + 2[/tex]
[tex]A_3 = 7 + 2[/tex]
So, we have:
[tex]A_1 = 5[/tex]
[tex]A_2 = A_1 + 2[/tex]
[tex]A_3 = A_2 + 2[/tex]
Express 2 as 3 - 1
[tex]A_3 = A_{3-1} + 2\\[/tex]
Substitute n for 3
[tex]A_n = A_{n-1} + 2[/tex]
Hence, the recursive formula is [tex]A_n = A_{n-1} + 2[/tex]
Read more about recursive and explicit formulas at:
https://brainly.com/question/11235928